An Analysis of Coal Seam Lithology using The Well-logging Method for Correlation of Location X, Musi Banyuasin Coalfields, South Sumatra - Lubis, Ashar Muda; Larang, Miranda Puspa; Fahmi, Khairul; Shah, Afroz Ahmad (Indonesian Journal on Geoscience, 2024)
South Sumatra region has abundant potential coal reserves, but the lack of structural and stratigraphic data makes it not be easy to map their total extent and to understand the genesis. These limitations can be partially resolved using the borehole well-logging methods. The aim of this research was to investigate correlation of coal seam lithology using the well-logging methods in a coalfield, location X, Musi Banyuasin, South Sumatra. The several exploration activities were conducted using the well-logging method to acquire gamma-ray logs and density logs data from seven boreholes, namely PMCBS12, PMCBS13, PMCBS14, PMCBS15, PMCBS16, PMCBS17, and PMCBS19 sites. WellCAD software was used during the data processing to derive logging data (gamma-ray and density logs), and Minex software was utilized to analyze the physical parameter correlation among boreholes. Borehole data analysis was carried out by analyzing the lithology contained in the borehole, especially to analyze the characteristics of the coal seam, such as depth and thickness. The results suggest that the thickness of the existing coal seam in area X is at seam 6 from a depth of about 2.95-19.95 m, with a coal seam thickness ranging from 1.85 m in the PMCBS12 to a thickness of 3.6 m in the PMCBS19 well. Two to three - vertically spread seams were found in each borehole with a thickness of about 0.35-3.6 m at various depths. Correlation results among boreholes show that the distribution of coal seams extends from the northwest to the southeast with a distribution direction of N300˚E/6˚.